Costly liquidation, interbank trade, bank runs and panics - Donaldson, R.Glen (Journal of Financial Intermediation, 1992)
Standard models of panics do not allow for trade between banks and assume that a run bank's liquidation costs are determined exogenously. We develop a model in which banks trade with each other and liquidation costs are determined endogenously in a strategic environment. The model reproduces a panic's characteristic fall in stock prices, rise in interest rates, and wave of bank runs. It also accounts for the seasonal timing of panics, the change in interest rates across panics, and international differences in panic frequency. The roles of withdrawal suspension, lender of last resort, and deposit insurance are also investigated.